Information Technology in Activities of the World’s Leading Libraries and Their Use under Modern Communications - Ірина Бородай; Людмила Татарчук; Тетяна Підгайна (Український журнал з бібліотекознавства та інформаційних наук, 2022)
The aim of the article is to highlight the main trends in the development and implementation of information and communication technology in the library service system of the world’s leading countries.